2016
DOI: 10.1021/acsphotonics.5b00536
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude- and Phase-Controlled Surface Plasmon Polariton Excitation with Metasurfaces

Abstract: Surface plasmon polaritons (SPPs) have shown high potential for various applications in various fields, ranging from physics, chemistry, and biology to integrated photonic circuits due to their the strong confinement of light to the metal surface. Exciting an SPP from a free-space photon in a controllable manner is an essential step toward more complex and integrated applications. Methods for coupling photons to SPPs are numerous, but in order to control the amplitude and phase of an SPP, most of these methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 26 publications
0
34
1
Order By: Relevance
“…A different set of SPP couplers are formed by arrays of anisotropic rectangular apertures in opaque metal films, which can convert CP light to SPPs . Lin et al experimentally demonstrated a spin‐dependent directional SPP coupler containing arrays of rectangular apertures with principle axes perpendicular to each other (see Figure d) .…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A different set of SPP couplers are formed by arrays of anisotropic rectangular apertures in opaque metal films, which can convert CP light to SPPs . Lin et al experimentally demonstrated a spin‐dependent directional SPP coupler containing arrays of rectangular apertures with principle axes perpendicular to each other (see Figure d) .…”
Section: Applicationsmentioning
confidence: 99%
“…As two columns with orthogonally oriented apertures are placed at a distance of quarter of SPP wavelength, the interference between launched SPPs yields directional SPP excitations dictated solely by the helicity of incident CP light (Figure d) . While such concept is already intimately linked with the PB concept, an alternative approach is to directly use PB metasurfaces . Arranging anisotropic apertures in a lattice with their principle axes rotating successively, the designed PB metasurface can provide spin‐dependent phase gradients to compensate the k‐mismatch between incident CP light and the eigen SPPs on the metal film.…”
Section: Applicationsmentioning
confidence: 99%
“…However, conventional imaging or holography techniques are usually limited by the amplitude‐ or phase‐only modulation schemes, which is not the full information of object images . Independently simultaneous control of amplitude and phase with metasurfaces requires more degree of freedom to manipulate the optical field, without introducing unpractical nanostructures . Kim et al proposed a nanorod gap‐surface plasmon resonator to form Huygens' metasurfaces in the optical waveband ( Figure a) .…”
Section: D Manipulation Of Optical Waves With Metasurfacesmentioning
confidence: 99%
“…Metasurfaces can support a rich variety of optical modes that enable a straightforward strong coupling of light in their subwavelength thickness. Furthermore, their optical response can be made broadly tunable through changes in their environment, enabling a dynamic shaping of the amplitude and phase of light . Such tunability also opens the way to using metasurfaces as “wireless” sensors allowing an optical monitoring of their environment.…”
mentioning
confidence: 99%